Electrophysiological studies of paraventricular and supraoptic neurones recorded in vitro from slices of rat hypothalamus. - Haller, E W (1980)
1. In slices (300 micrometer) of rat hypothalamus maintained in vitro in isotonic (298 +/- 4 m-osmol/kg) medium, the median firing rate of twenty-four supraoptic (s.o.) neurones was 0 . 05 spikes/s, compared to 0 . 66 spikes/s for twenty-eight paraventricular (p.v.) units (P < 0 . 01) and 0 . 79 spikes/s for forty-three anterior hypothalamic area a.h.a. units (P < 0 . 001). 2. One hundred and two p.v. and s.o. units incubated in hypertonic medium (311--343 m-osmol/kg, achieved by adding NaCl) showed no correlation with osmotic pressure and displayed a similar level of spontaneous activity to units recorded in isotonic medium. Recordings from nineteen p.v. and s.o. units during rapid changes from iso- to hypertonic (338 +/- 4 m-osmol/kg) medium confirmed this lack of osmo-sensitivity. 3. Excitation of s.o. units in vitro with glutamate resulted in firing patterns similar to those found in previous in vivo studies on activated s.o. cells. Thus out of thirty-two glutamate-excited units, twelve (37%) fired in repetitive bursts, giving a phasic pattern and thirteen (41%) showed fast continuous activity. The remaining seven (22%) units showed ambiguous patterns that were neither continuous nor clearly phasic. 4. Mean durations of bursts and silent periods in phasic cells excited by perifused glutamate were 16 . 6 s and 13 . 2 s (calculated from normalized distributions of thirty values), compared to means of 41 . 7 s and 33 . 9 s (thirty-six values, P < 0 . 001 for each parameter) for cells excited by glutamate ionophoresis. The periodicity of phasic firing in vitro was unaffected by a change to hypertonic (340 m-osmol/kg) medium. 5. From these in vitro results it is proposed that the excitation associated with osmotic stimuli in vivo does not originate within the p.v. and s.o. neurosecretory cells, but that it involves a separate osmoreceptor. However, the control of phasic firing, which is commonly found during osmotic excitation, would seem to involve a mechanism which lies within or in close proximity to, the neurosecretory neurones.